Complications in the Enteral Nutrition - Erhan, Ömer Lütfi; Akın, Mustafa (Fırat University, 2001)
Although enteral feeding is associated with fewer life-threatening complications, it is nonetheless a medical therapy in which complications can develop. All too often, enteral feeding is not given the attention it deserves. The most frequent complication attributed to tube feeding is diarrhea. This problem, is usually caused by factors unrelated to enteral feeding (such as medications or bacterial enterotoxins). GI complications are often corrected by selecting a more appropriate formula based on the patient's clinical condition or by adjusting the feeding rate or schedule. Mechanical complications are easily avoided by using a nasoenteric tube designed for enteral feeding, and by routinely flushing the feeding tube with water. Metabolic parameters also must be monitored closely and routinely during enteral therapy. Patients are at the greatest risk for metabolic complications during the first few weeks of nutritional therapy.

Enteral beslenmeyle ilgili yaşamı tehdit edebilen birkaç komplikasyon bulunmasına rağmen, bunların gelişimi medikal tedavinin sonucu olabilmektedir. Sık görülenlerin tümü enteral nütrisyona hak ettiği özenin gösterilmemesinden dolayıdır. Tüple beslenmenin en sık komplikasyonu diyaredir. Bunun oluşumundaki faktörler (ilaçlar, bakteriyel endotoksinler..) çoğunlukla tüple ilişkili değildir. Gastrointestinal komplikasyonlar hastanın klinik durumuna daha uygun formülün seçilmesi veya beslenme tablosu/hızının değiştirilmesiyle düzeltilir. Mekanik problemler enteral beslenmeye uygun nazoenterik tüpün seçilip kullanılmasıyla ve rutin olarak tüpün içinin yıkanmasıyla kolayca kaçınılabilir konuma gelmektedir. Metabolik parametreler de sıkı olarak monitörize edilmelidir. Nütrisyonel tedavinin ilk birkaç haftasında metabolik komplikasyon için hastalarda en büyük risk vardır.
ENTERAL NÜTRİSYONDA KOMPLİKASYONLAR